Reconstructing the hepatocellular carcinoma microenvironment: the current status and challenges of 3D culture technology - Ting Xiong; Kai Wang (Discover Oncology)
Abstract Hepatocellular carcinoma (HCC), with high incidence and mortality rates among digestive system diseases, has become a focal point for researchers. However, the more we learn about HCC, the more apparent it becomes that our understanding is still superficial. The successes and failures of numerous studies underscore the urgent need for precision medicine in cancer treatment. A crucial aspect of preclinical research in precision medicine is the experimental model, particularly cell culture models. Among these, 3D cell culture models can effectively integrate and simulate the tumor microenvironment, closely reflecting the in vivo conditions of patients. This capability provides a solid theoretical foundation for personalized treatment approaches. In this review, we first outline the common in vitro 3D cell culture models and examine the essential elements within the tumor microenvironment, followed by insights into the current state and future developments of 3D in vitro cell models for HCC.